Objetivos Baseados em Valores na Definição de Ações do SSM: Estudo de Caso na Inclusão de Estudantes NEE - Francozo, Rafael Verao [UNIFESP] (2019)
Real world problems are complex, and this complexity translates into the absence of elements that allow us to define objectives, constraints, and resources, in addition to, what the actual problem to be considered is. Such problems may require broad changes in underlying policies, assumptions, and objectives, making it necessary to define clearly the real problems to be addressed and the true objectives to be reached. Education for students with special educational needs is a complex problem with context-dependent dynamics that are difficult to address. This study developed an approach to identify and define undesirable states in a given problem situation. In addition, the designed models led to a more desirable state in accordance with the objectives of those involved. To achieve this objective, an approach based on problem structuring methods was built to: 1) Focus on the context of a problematic situation under consideration; 2) Define objectives based on stakeholder values; and 3) Steer the situation towards change in line with the defined objectives. The constructed approach was applied in a teaching unit to address the issue of education for students with special educational needs. The application of the approach resulted in benefits such as the clear definition of how education for these students is understood in the institution, with special attention to the target audience regardless of clinical report. It also helped to identify the real problems and goals, by deconstructing established concepts. This study contributes to the specialized literature on Operational Research by guiding systemic planning for objectives based on stakeholder values. This contribution helps to set limits, guide, and prioritize the planning of necessary changes. As a social contribution, the study provides a structured means to identify the necessary practices for the effective inclusion of students with special educational needs, which helps to make society more inclusive, humane, and supportive.